COVID-19: Innovative Antiviral Drugs Required for Long-Term Prevention and Control of Coronavirus Diseases - Ratcliffe, Norman A.; Castro, Helena C.; Paixão, Izabel C.; Mello, Cicero B. (Current Medicinal Chemistry, 2021)
The COVID-19 pandemic has had global catastrophic effects on financial markets, jobs and peoples’ lives. Future prevention/therapy of COVID-19 will rely heavily on vaccine development and attempts to repurpose drugs previously used for other microbial diseases. Little attention, however, has been paid to possible difficulties and delays in producing these drugs. Sometimes, unfortunately, these endeavours have been politicized and if these two approaches founder in any way or resistance subsequently occurs, then the world will be left once again to the mercy of these devastating viral pandemics. This review, therefore, briefly outlines the challenges in the development of vaccines and repurposed antiviral drugs, which will hopefully lead to new treatments for COVID-19. It also concludes, however, that the armoury against COVID-19 urgently needs to be enlarging due to the potential severity and likely future reoccurrence of new emergent viruses. Therefore, serious consideration is given to alternative ways of preventing and controlling these pathogens that have received scant attention from the media in the present pandemic. The development of innovative, broad-spectrum, antiviral drugs from natural products is therefore particularly advocated with the challenges involved by new regulatory and scientific initiatives.
Keywords: antivirus